(untitled) (Acta Scientiarum. Agronomy, 2011)
The aim of this paper was to compare the morphological attributes and production components of the wild-type Baronesa cultivar potato with those of Baronesa potato plants that have been genetically modified using the potato virus Y coat protein (CP) gene. The experiment was conducted under greenhouse conditions (Biosecurity Quality Certificate no. 081/98 issued by the National Biosecurity Technical Committee) at the Federal University of Pelotas (UFPel), Pelotas-RS. The shoot and root lengths and the mean leaf number were determined six times at 14-day intervals after sowing; the length, width and fresh weight of the tubers were measured during the last harvest, which occurred 84 days after sowing. There were no statistical differences between the two genotypes with respect to morphological attributes or production components.